Analisis Tingkat Perkembangan Wilayah Kecamatan di Kota Padang Periode 2005-2019 - Wulan Sri Handayani (JURNAL BUANA, 2022)
This study aims to 1) Determine the level of development of the sub-district in Padang City in 2005-2019. 2) Knowing service centers in Padang City in 2005 and 2019. This type of research is quantitative descriptive. The data used is secondary data obtained by agencies such as the Central Statistics Agency and the Padang City Public Works Service. To determine the level of regional development using an analysis of the composite index table and classifying several variables contained in the regional development indicators. The results of this study indicate that regional developments in Padang City from 2005 to 2019 experienced high or advanced development in Koto Tangah District, Nanggalo District and Lubuk Kilangan District, these results are due to the fact that these three sub-districts always experience development or increase in the number of socio-economic facilities. as well as the population. As for the areas that experience low development, there are Bungus Teluk Kabung Districts which are very far from the city center. To find out the regional service centers in Padang City in 2005 and 2019 using the scalogram method and the masrhall centrality index. The results of this study indicate that the service centers in Padang City in 2005 and 2019 which occupy the first order are in the West Padang District and the lowest order V is in the Bungus Teluk Kabung sub-district. The service center is located in West Padang District because this sub-district is the center of economic growth.